Translation of the Holy Quran - Legitimacy and scholars opinion - Hossain, Mohammed Bahaa Eddin (IIUC Studies, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–>The full text of this article is in Arabic - see PDF below. doi: 10.3329/iiucs.v3i0.2681 IIUC STUDIES Vol. - 3, December 2006 (p 133-144